2015
DOI: 10.1021/acsmacrolett.5b00038
|View full text |Cite
|
Sign up to set email alerts
|

Selective Nucleation of Poly(3-hexyl thiophene) Nanofibers on Multilayer Graphene Substrates

Abstract: We demonstrate that graphene surfaces provide highly selective nucleation of poly(3-hexyl thiophene) (P3HT) nanofibers (NFs) from supersaturated solutions. Solvent conditions are identified that give rise to a wide hysteresis between crystallization and melting centered around room temperature, yielding metastable solutions that are stable against homogeneous nucleation for long periods of time but that allow for heterogeneous nucleation by graphene. Selective growth of P3HT crystals is found for multilayer gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
26
0

Year Published

2016
2016
2018
2018

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 37 publications
1
26
0
Order By: Relevance
“…The optoelectronic effects in semicrystalline conjugated polymers depend sensitively on chain order and the way crystalline domains are interconnected and oriented . 1D nanostructures such as nanowires, nanotubes, nanofibers, nanowire shish‐kebab (NWSK) structures, micro/nano conductive–dielectric channels, needle‐like lamellae, and sandwiched conductive–dielectric–conductive structures have attracted particular attentions due to their unique electronic and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…The optoelectronic effects in semicrystalline conjugated polymers depend sensitively on chain order and the way crystalline domains are interconnected and oriented . 1D nanostructures such as nanowires, nanotubes, nanofibers, nanowire shish‐kebab (NWSK) structures, micro/nano conductive–dielectric channels, needle‐like lamellae, and sandwiched conductive–dielectric–conductive structures have attracted particular attentions due to their unique electronic and optical properties.…”
Section: Introductionmentioning
confidence: 99%
“…Indeed, the surface energy, which was in a direct correlation with the contact angle did not conspicuously affect the P3HT orientation. It was demonstrated that the orientation of P3HT chains depends on the π‐π interactions between the thiophene rings and graphenic surface . Therefore, in the current work, we functionalized and grafted the surface of rGO to manipulate these interactions.…”
Section: Resultsmentioning
confidence: 95%
“…Surface scans of PMMA-graphene and PDA coated PMMA-graphene ( † ESI Figure S10) were acquired using the Cypher ES atomic force microscope (Asylum Research, Santa Barbara CA). 107 Samples were imaged in AC mode with Tap-300G cantilevers (Budget Sensors).…”
Section: Methodsmentioning
confidence: 99%